The new mole: paths of the Latin American left - Sader, Emir (London, 2011)
"An authoritative discussion of major recent developments in Latin American politics, by one of the continent's leading political thinkers. Sader seeks to explain the resurgence of radicalism in the region by placing it in historical context, and exploring the theoretical resources on which it has drawn. The book is unusual in combining succinct judgments with broad chronological and geographical sweep-covering a period running from the early twentieth century to the present, and embracing the lands from Chile to Mexico. Sader points to areas where Latin America can propose new thinking to the world-on indigenous questions, for example-and areas where political thought lags behind practice, as in Venezuela. He also highlights once more the importance of the processes of regional integration under way in Latin America, which stand out because they are occurring independently of Washington. The book concludes by pointing to the role social, political and ideological struggles will play in defining the continent's trajectory as it exits the hegemonic crisis-an optimistic affirmation of agency that is all the more convincing for its sobriety. "